Titanium dioxide nanoparticles applied as ultraviolet radiation blocker in the polylactic acid bidegradable polymer. (August 2019) - Mohr, L.C.; Capelezzo, A.P.; Baretta, C.R.D.M.; Martins, M.A.P.M.; Fiori, M.A.; Mello, J.M.M.
Abstract: Titanium dioxide nanoparticles have been widely studied because of its photocatalytic effect and capacity to block ultraviolet (UV) radiation. In this work we incorporated 1 wt% and 5 wt% dioxide titanium nanoparticles (TiO2 -NPs) on biodegradable polymer Ecovio ® for the purpose to block UV radiation. The polymer with and without TiO2 -NPs were submitted to optical characterization by absorbance and light transmittance tests, thermal and mechanical analysis (DSC and stress-strain tests and biodegradation tests. The results showed that the incorporation of TiO2 -NPs in the Ecovio ® modifies its light transmission characteristics of the ultraviolet and visible light and can be considered a form of ultraviolet radiation blocking. The best results for the ultraviolet blocking were obtained with polymeric films with 5 wt% TiO2 -NPs, providing a new propriety to biodegradable polymer making possible its future application in packing, for example. The mechanical properties of the Ecovio ® films were modified when the TiO2-NPs were incorporate. The polymeric films became more flexible but less resistant and a new crystalline phase were observed (phase β and phase γ). The incorporation of the TiO2-NPs into the biodegradable polymer provided the production of a greater amount of CO 2 from the respirometry process of the microorganisms. These characteristics are possibly associated to the photocatalytic activities of TiO2 NPs. The results after respirometry test showed that the biodegradation processes in soil at room temperature during the 90 days was not complete, requiring a longer time for the mineralization of the samples. The present work shows that biodegradable films developed have potential application for biodegradable packaging with blocking of UV radiation. Highlights: Ecovio ® biodegradable polymer films with TiO2 -NPs were obtained. TiO2 -NPs acted as ultraviolet radiation blockers in polymer films. New crystalline phases were generated in the polymer films with TiO2 -NPs. There were modifications in the mechanical properties of the films with nanoparticles. Polymeric films with TiO2 -NPs released more CO2 in the biodegradation test which can be justified by the photocatalytic decomposition of the polymer, caused by TiO2 -NPs.